Evaluation Of The Use Of The Integrated Referral System (SISRUTE) In Health Facilities In North Bengkulu Regency In 2023 - Muhammad Rifki El Muammary; Risky Kusuma Hartono (Jurnal EduHealth, 2024)
SISRUTE, an application that connects patient data between health facilities, is faced with obstacles such as data incompatibility and dependence on internet stability. Even though it started in 2020 in North Bengkulu, only 22.7% of health facilities have adopted it, especially community health centers. Implementation obstacles include staff, IT infrastructure, commitment of referring hospitals, patient conditions, and slow response.Usability testingneeded to improve health referral services. The aim of this research is to analyze the evaluation of the use of the Integrated Referral System (SISRUTE) inmedical facilityNorth Bengkulu Regency in 2023. This research is a mix methods research. The research instrument was a questionnaire which was analyzed using univariate analysis, bivariate analysis and multivariate analysis as well as observation and in-depth interviews with informants. Research analysis shows that perceived usefulness, ease of use, and intensity of use have a significant effect on attitudes and use of SISRUTE in hospitals. Attitude towards use is proven to mediate the relationship between perceived usefulness, ease of use, and intensity of use with SISRUTE use. Perception of usefulness has the greatest influence on the use of SISRUTE. Factors such as management support in the form of monitoring and evaluation of use, staff training, health infrastructure, government support, and financial issues influence the acceptance and use of SISRUTE in North Bengkulu Regency. Evaluation of the use of SISRUTE that needs to be carried out is increasing the efficiency of patient referrals, user satisfaction, and identifying areas of improvement such as monitoring and evaluating use.